Contribution of endothelium-derived hyperpolarizing factor to exercise-induced vasodilation in health and hypercholesterolemia. (February 2015) - Ozkor, Muhiddin A; Hayek, Salim S; Rahman, Ayaz M; Murrow, Jonathan R; Kavtaradze, Nino; Lin, Ji; Manatunga, Amita; Quyyumi, Arshed A
The role of endothelium-derived hyperpolarizing factor (EDHF) in either the healthy circulation or in those with hypercholesterolemia is unknown. In healthy and hypercholesterolemic subjects, we measured forearm blood flow (FBF) using strain-gauge plethysmography at rest, during graded handgrip exercise, and after sodium nitroprusside infusion. Measurements were repeated afterl -NMMA, tetraethylammonium (TEA), and combined infusions. At rest, l -NMMA infusion reduced FBF in healthy but not hypercholesterolemic subjects. At peak exercise, vasodilation was lower in hypercholesterolemic compared to healthy subjects (274% vs 438% increase in FBF, p =0.017). TEA infusion reduced exercise-induced vasodilation in both healthy and hypercholesterolemic subjects (27%, p <0.0001 and −20%, p <0.0001, respectively). The addition ofl -NMMA to TEA further reduced FBF in healthy (–14%, p =0.012) but not in hypercholesterolemic subjects, indicating a reduced nitric oxide and greater EDHF-mediated contribution to exercise-induced vasodilation in hypercholesterolemia. In conclusion, exercise-induced vasodilation is impaired and predominantly mediated by EDHF in hypercholesterolemic subjects.Clinical Trial Registration Identifier: NCT00166166